A replication of "Representative bureaucracy and the willingness to coproduce". (16th May 2021) - Sievert, Martin
Abstract: Research on symbolic representation suggests that citizen–state interactions might benefit from public organizations' representativeness. Recent experiments on symbolic gender representation provide contradictory findings regarding the influence on citizens' co‐production intentions. This study conducts a wide replication based on new data to reexamine the positive impact of symbolic gender representation identified by Riccucci et al. (2016, Public Administration Review, 76(1), pp. 121–130). The applied survey experiment closely resembles the original design aspects. The experiment is set in criminal justice policy, a policy field featuring co‐production of core public services such as prisoner rehabilitation. The results do not confirm a positive effect of symbolic gender representation on willingness to co‐produce. Instead, several arguments point to citizens' perceptions of uncertainty related to the co‐production context and procedures as a boundary condition for the effects of symbolic gender representation.